Diseño de estrategias metodológicas para la enseñanza aprendizaje de los fundamentos técnicos del fútbol sala en los estudiantes de sexto año de e.g.b en la unidad educativa Oxford en el cantón Salcedo, periodo 2014-2015 - Jiménez Albán, Adán Euclides (2015)
This research aims to design methodological strategies for the right process of learning of the technical fundamentals of soccer the hall for students in the sixth year of basic education. The was raised as a problem abandoning that is given to the practice of this sport, also it serves to go motivating children to the development of all physical abilities. Soccer the hall is a form adapted for soccer game in a confined space